An Analysis on Students’ Reading Comprehension Difficulties in Narrative Text at SMA Muhammadiyah Bangkinang - Fauzia, Yesi; Rianti, Wida; Asilestari, Putri (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
This research is motived by the problems faced by students because student have difficults in reading comprehension the narrative text, such as difficulties to finds detail, translating new words, finding main ideas and making inferences. The purpose of this study is to determine the students’ reading comprehension difficulties in Narrative text. This study use a qualitative research design. The sample of this research is Tenth grade students of SMA Muhammadiyah Bangkinang. In the study, the research use questionnaire as an instrument of collecting data. In analysis of data, the reseach steps are coding, data reduction, data display and conclusion. Based on the result of research through questionnaire, most of the student chose “Strongly Agree” with the statement that they haad difficulty in learning to read. It can be conclude that the result are students difficult to understanding long sentence and text because lack of vocabulary, grammar and remember, difficult to understand the reading text before knowing the topic and background, students read slowly and carefully, reread ,summarize in they own word, translate English into their native language, to understand the text and difficulty in concentration